AB0315 Reduction of Concomitant Oral Methotrexate or Corticosteroids in Combination Treatment with Adalimumab Does Not Affect Effectiveness in Patients with Rheumatoid Arthritis. (15th July 2016) - Keystone, E.; Breedveld, F.; Kavanaugh, A.; Zhang, Y.; Sainsbury, I.; Kalabic, J.
Abstract : Background: In rheumatoid arthritis (RA) patients (pts) receiving corticosteroids (CS) or methotrexate (MTX) with an anti-TNF, such as adalimumab (ADA), the concomitant CS or MTX dose may be reduced if pts respond well or have side-effects. Objectives: To assess treatment effectiveness in pts whose MTX or CS oral dose was reduced over 10 years (y) of open label (OL) ADA treatment. Methods: This was observed data from OL extensions (OLE) of the PREMIER and DE019 trials. 1, 2 In PREMIER, MTX-naïve, early RA pts received ADA/MTX/ADA+MTX for 2y, and optional OL ADA for upto 8y. In DE019, biologic-naïve, established RA pts received 20 mg ADA+MTX/ 40 mg ADA+MTX/PBO+MTX for 1y and optional OL ADA+MTX for upto 9y. In both OLEs, MTX could be added/adjusted at the investigator's discretion, and oral CS dose could be tapered in pts who responded. Effectiveness at final visit (FV) was assessed by the numbers of pts achieving TJC68 =0, SJC66 =0, improvement from baseline in HAQ-DI ≥0.5 (HAQ-DI 0.5), ACR20/50/70 criteria and 28-joint disease activity score based on C-reactive protein (DAS28-CRP)<2.6. Additionally, in PREMIER, modified EULAR remission (REM) criteria [DAS28-CRP <2.6, TJC68 ≤1, SJC66 ≤1], "Good EULAR response" [DAS28-CRP <3.2 with a change from baseline ≤-1.2] were used. Results: In PREMIER, by the pt's FV, out of 375 pts who had any oral CS, 220 (58.7%) were on ongoing CS; 155 (41.3%) had stopped. Among the 375 pts, 32% had a stable CS dose and 26.1% had a CS dose reduction. Dose reduction did not affect the proportion of pts reaching ACR criteria, HAQ-DI 0.5, and DAS28-CRP <2.6 by FV (table ). Out of 497 pts in the OLE, 261 (52.5%) used concomitant MTX in the OLE, 236 pts did not. With/without MTX, the number of pts with DAS28-CRP<2.6 increased from 2 to 10y, and the proportion of pts with SJC or TJC=0, good EULAR response, or modified EULAR REM criteria, and the HAQ-DI scores were comparable in the +/− MTX groups. In DE019, by the pt's FV, out of 352 pts who received any oral CS, 207 (58.8%) were on ongoing CS and 145 (41.2%) had stopped CS. Among the 352 pts, 141 (40%) had a stable CS dose and 82 pts (23.3%) had a dose reduction. Out of 550 pts on MTX during the study, 497 (90.4%) were receiving MTX, and 53 (9.6%) had stopped by FV; 345/550 pts (62.7%) had stable MTX and 158 (28.7%) had a reduction. Reduction of CS or MTX did not affect the proportion of pts who reached the ACR criteria, HAQ-DI 0.5 and DAS28-CRP <2.6 by FV. Conclusions: Overall, effectiveness associated with continuous ADA treatment was not sacrificed in pts in whom concomitant oral CS or/and MTX doses were reduced or discontinued, although many of these pts were likely responding well at the time of taper. References: Keystone et al. J Rheum 2013;40:1487–97; Keystone et al. J Rheum, 2014;41:5–14 Acknowledgement: AbbVie: study sponsor, contributed to design, data collection, analysis, interpretation; in writing, reviewing and approval of final version. Medical writing support: Naina Barretto of AbbVie. Disclosure of Interest: E. Keystone Grant/research support from: AbbVie, Amgen, AstraZeneca, BMS, Janssen, Pfizer, Roche, and UCB, Consultant for: AbbVie, Amgen, AstraZeneca, BMS, Janssen, Pfizer, Roche, and UCB, Speakers bureau: AbbVie, Amgen, AstraZeneca, BMS, Janssen, Pfizer, Roche, and UCB, F. Breedveld Consultant for: Centocor, Schering-Plough, Amgen/Wyeth, and AbbVie, A. Kavanaugh Grant/research support from: AbbVie, Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB, Consultant for: AbbVie, Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB, Y. Zhang Shareholder of: AbbVie, Employee of: AbbVie, I. Sainsbury Shareholder of: AbbVie, Employee of: AbbVie, J. Kalabic Shareholder of: AbbVie, Employee of: AbbVie